CLOUD-POWERED e-HEALTH - Liviu Cristian STEFAN; Logica BANICA (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2013)
During the last years, the global economic crisis has affected all domains, including the health sector. Many governments have considered that the solution to this problem is to reduce public expenses on healthcare, to decrease the budgets for health services, to rationalize the medical plans for the population, to increase the share of health expenditure paid by patients and to select the products on the pharmaceutical market.In order to improve the medical service whilst maintaining reduced infrastructure costs, the new digital technologies offer the solution of cloud-based services for the e-health systems.In this paper we present the cloud-hosted healthcare applications concept, the advantages of using e-Health on distributed platforms and some considerations about the security levels. Also, we further present an experiment based on the free OpenEMR solution, which has also a cloud version, ZH-Services OpenEMR.